Transcultural theater - Heeg, Günther (Routledge, 2023)
"Transcultural Theater outlines the idea of a transcultural theater as enabling an approximation to and an interaction with the foreign and the alien. In consideration of the allure of fundamentalist and populist movements that promote the development and practices of xenophobia worldwide, this book makes a powerful plea for the art of theater as a medium of conviviality with (the) foreign(er) that should not be underestimated. This study contributes to transcultural experience, artistic practice, and education in the medium of theater. The book's investigation extends far into space and time and pays particular attention to the relationship between aesthetic experience, artistic practice, and academic representation. This book is for scholars and students as well as for all those working in the cultural field, especially in the field of cultural transfer"--